PENGARUH PENERAPAN EMPLOYEE STOCK OPTION PLAN PADA NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Hutnaleontina, Putu Nuniek; Suputra, I Dewa Gede Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aimed to get empirical evidence of the effect of 1) the proportion of employee stock options were granted to the company's performance, 2) the company's performance in the company's value, 3) the proportion of employee stock options are granted on the value of the company, 4) the proportion of employee stock options were granted at a value the company through financial performance. This research was conducted in the Indonesia Stock Exchange with secondary data. The sampling technique is purposive sampling. The population used in this study are 36 companies that have adopted and announced ESOP from January 1, 1999 until December 31, 2014. The theory underlying this study is the Agency Theory and Prospect Theory. The results showed that the proportion of stock options the company after the grant 1) a positive effect on financial performance, 2) financial performance has positive effect on the value of the company, 3) the proportion of stock options has no direct effect on the value of the company, 4) the proportion of stock options has no effect on the value of the company through the mediation of the financial performance of the company, so it can be concluded the company's financial performance perfect mediate the relationship between the proportion of the number of shares granted on the value of the company after the grant .
Keywords: Employee Stock Option Plan, Company Performance, Value Company